ANTIBACTERIAL ACTIVITY OF KELAKAI AND KATUK LEAVES EXTRACT COMBINATION IN COMPARISON TO 1% Povidone iodine AGAINST Aggregatibacter actinomycetemcomitans - Siti Denty Rizqita; I Wayan Arya Krishnawan Firdaus; Isnur Hatta (FKG Unlam, 2023)
Background: Aggregatibacter actinomycetemcomitans is one of the causes of aggressive periodontitis. Povidone iodine mouthwash at 1% concentration can be used to reduce the growth of these bacteria, but long-term use may lead to side effects that initiate the need for an alternative herbal mouthwash. Kelakai leaves contain antibacterial substances such as flavonoid, tannin, alkaloid and steroid, while katuk leaves contain flavonoid, tannin, alkaloid and saponin. Combination of these two extracts can be used to increase the effectiveness produced. Objective: To prove that the antibacterial activity of kelakai and katuk leaves extract has the same effectivity as 1% Povidone iodine against Aggregatibacter actinomycetemcomitans. Methods: True experimental method with post-test only and control group design was applied in this study. The antibacterial activity test was performed using diffusion method in 13 treatment groups with triple repetition. The total samples used were 39 samples. The treatment groups were the combination of kelakai leaves extract with 25%, 50%, 75%, 100% concentration and katuk leaves extract with 20%, 40%, 80% concentration, and 1% Povidone iodine. The parameter measured was the inhibitory zone (mm). Results: Combination of 100% kelakai leaves and 80% katuk leaves extract has the highest inhibitory zone of 17.33 mm. Post Hoc Bonferroni test results showed that the combination of 75% kelakai leaves and 80% katuk leaves extract were the only group that had no significant difference to 1% Povidone iodine. Conclusion: Combination of 75% kelakai leaves extract and 80% katuk leaves extract is statistically equivalent to 1% Povidone iodine against Aggregatibacter actinomycetemcomitans. Keywords: Aggregatibacter actinomycetemcomitans, inhibitory zone, katuk leaves extract, kelakai leaves extract, 1% Povidone iodine.